Accelerating transition toward district heating-system decarbonization by policy co-design with key investors: opportunities and challenges - Auvinen, Karoliina; Meriläinen, Teemu; Saikku, Laura; Hyysalo, Sampsa; Juntunen, Jouni K. (Taylor & Francis, 2023)
District heating in European, Chinese, and Russian cities is still mainly produced with fossil fuels. Energy-system reconfiguration is essential to achieve full decarbonization, which calls for a greater understanding of how to engage key investors in market transformation and how to formulate effective policy mixes. This article reports on how decarbonization could be accelerated in district-heating systems in Finland with stakeholder orientation especially on key investors consisting of companies focused on district-heating, data-center management, real estate development, and sewage operations. The technological attention is on the excess and ambient heat systems. Drawing from surveys, interviews, and workshops we identified investment barriers and collected policy and strategy proposals to overcome them. The results demonstrate that diversifying and strengthening the policy and strategy mix is needed to overcome barriers related to profitability, political uncertainties, and underdeveloped cooperation and profit-sharing models. Policy co-design with key investors holds potential to improve the effectiveness and acceptability of policies, but with certain limitations as regime actors tend to oppose the types of destabilization needed to achieve full decarbonization of energy systems. Thus, effective policy co-design processes need further development as collaboration is a success factor to achieve climate change-mitigation targets, but simultaneously tensions and conflicts cannot be avoided when accelerating energy-system transformation.
Keywords: energy transition; decarbonization; heat pumps; policy mix; co-design; Finland; district heating; fi=Tuotantotalous|en=Industrial Management|